Strategy for Developing Fisheries Sme’s Based on Processed Milk and Seaweed Using Electric Shock Pasteurization Tecnology - Zainal Abidin; Eko Waluyo; Wahyu S. Utomo (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Seaweed is one of the leading aquaculture commodities. Seaweed contains many enzymes and fiber that are good for health. So that the selling value of seaweed does not fall, for example, the SME’s Poklahsar "Citara" processes Euchema cottonii seaweed and fresh cow milk into various processed seaweed, namely yogurt, milk, drinks, candy and jelly drink seaweed. The purposes of this study are to analyze internal and external factors that become strengths, weaknesses, opportunities, and threats to business development; formulate strategies and priorities for business development strategies. This descriptive method research determines the respondent with purposive sampling. Qualitative analysis of the internal, external and industrial environment. Quantitative descriptive analysis to analyze financial aspects, Internal Factor Evaluation matrix, External Factor Evaluation matrix, Internal-External matrix, SWOT analysis, and Quantitative Strategic Planning Matrix analysis. The results show that the business development strategy in Poklahsar "Citara" occupies a growth and development strategy, utilizing high opportunities and strengths to support aggressive growth policies. The priority of the development strategy is to optimize business and prayer for all work done, especially in terms of the integration of management of production-marketing-financial-prayer.